The Implementation of Authentic Assessment in Improving Learning Outcomes in Islamic Religious Education: A Study of Students at SDN Trasak 2 - Agus Rudiyanto (JOSAR (Journal of Students Academic Research), 2026)
Learning assessment is a crucial component in determining the success of the educational process. However, assessment practices in Islamic Religious Education (IRE) at the elementary school level often focus solely on cognitive aspects, failing to fully capture students’ comprehensive abilities. This situation calls for the implementation of a more comprehensive assessment model, such as authentic assessment as recommended in the Merdeka Belajar Curriculum. This study aims to analyze the implementation of authentic assessment and its impact on improving student learning outcomes in the PAI subject at SDN Trasak 2. This is a field research study using a descriptive qualitative approach. Data were collected through observation, interviews with teachers and students, as well as a review of relevant documentation and literature to obtain an overview of the implementation of authentic assessment in the learning process. The results of the study indicate that the implementation of authentic assessment is capable of improving student learning outcomes more comprehensively, not only in the cognitive aspect but also in the affective and psychomotor dimensions. Furthermore, the implementation of authentic assessment encourages students’ active engagement in the learning process, thereby creating a more meaningful learning experience and enhancing learning motivation. Teachers also gain deeper assessment insights into students’ skill development, enabling them to provide more precise feedback. This study concludes that authentic assessment is an effective evaluation approach in supporting the implementation of the Merdeka Curriculum in Islamic Education (PAI) at the elementary school level. The implications of this research highlight the importance of strengthening teachers’ competencies in designing and implementing authentic assessment to improve the quality of learning and student learning outcomes.